Kulturna pokrajina Haloz (University of Maribor Press, 2019)
The Cultural Landscape of Haloze Region. The cultural landscape is a result of the human action, which in turn is connected to economic and social conditions. That is why the modern cultural landscape is changing from agrarian to more or less urbanized. The monograph deals with the cultural landscape of Haloze from several perspectives. These include changing land use categories that indicate a decline in agricultural activity. The presentation of changing demographic conditions in Haloze settlements shows the increasing differentiation of the landscape into demographically more and less stable parts. The review of agriculture, once the most important economic activity of the area, shows major structural changes in the field; changes that will become even bigger in the coming years. The development of tourism shows the increasing importance of this sector. The monograph addresses the pedological conditions from the point of view of sustainable agriculture and self-provisioning, as well as the natural potentials of the area, as a basis for planning new activities, specifically recreational areas and cycling trails. The marginal character of Haloze is also discussed from various aspects that are addressed by the term marginality. The monograph concludes with a text about social groups that create the cultural landscape. Two articles present the life and work of Vladimir Bračič, a geographer and the first rector of the University of Maribor, who this monograph is dedicated to.